Associated Factors for Erectile Dysfunction Occurrence in Patients with Coronary Artery Disease: A Cross-sectional Study - Ali Hamidi Madani; Fardin Mirbolouk; Mona Naghshbandi; Tolou Hasandokht; Mahboobe Gholipour; Mohammad Sajjad Zabihi; Mohammad Hamidi Madani (Iranian Journal of Medical Sciences)
Background: Erectile dysfunction (ED) is associated with cardiovascular events, and a significant proportion of men with coronary artery disease (CAD) exhibit early signs of ED. Moreover, both of these disorders shared common risk factors in previous studies. This study was conducted to determine which risk factors and conditions in CAD patients might contribute to the occurrence of ED.Methods: This analytical cross-sectional study was conducted in the North of Iran from October 2016 to September 2017. 316 patients with coronary artery disease were enrolled. Demographic information were collected using a checklist, and the International Index of Erectile Function (IIEF-15) questionnaire  was used to determine the participant’s ED status. Univariate and multivariate logistic regression were used to investigate associated factors.Results: The mean age of the participants was 56.51±9.88 years. About 55.1% of the patients had ED. Moreover, the severity of CAD was independently associated with an increased risk of ED (OR=4.11, 95%CI=1.69-9.97), with patients having more than one involved coronary artery and greater coronary artery stenosis had a higher risk of developing ED occurrence (OR=3.74, 95%CI=1.72-8.09). Besides, age (OR=1.23, 95%CI=1.18-1.29) and BMI (OR=1.26, 95%CI=1.13-1.41) were independent predictors of ED occurrence in CAD patients. Conclusion: Higher CAD severity, older age, and higher BMI were all independent predictors of ED occurrence in CAD patients. While, diabetes mellitus, dyslipidemia, and smoking were not independent risk factors, they could contribute to the development of ED when combined with other risk factors.